Overview of Costa Rica's tourist competitiveness - Suárez-Matarrita, Leonardo (2021)
The evaluation of the competitiveness of the tourist industry of a destination or country begins with the analysis of the indicators and metrics that have been developed for this purpose. The service delivery characteristic makes the indicators quantitative and qualitative, making their assessment more complex. Two methodologies are used to measure the metrics. The Travel and Tourism Competitiveness Index, which allows the analysis and global positioning between countries, to serve as a comparison to the different economic agents that make investments in the sector. Additionally, in Costa Rica, the Costa Rican Tourism Institute collects the indicators of this activity, through the methodology of applying surveys, and the results are not presented as an index, but as observable figures and statistics. This country is one of the main tourist destinations in the world, for bringing together the components to meet the expectations of the travelers who visit each year. Thanks to the diversity of flora, fauna and scenic beauty, the country has positioned itself among the best 50 places worldwide, according to its competitiveness since 2007. This work shows the panorama of the indicators of the country's tourist activity in function of both methodologies, indicators, and metrics, according to the behavior of the trend over time and competitive advantages. Both methodologies allow us to assess the growth of the travel and tourism industry and the benefits for the sustainable development of the country.